ANALISIS SEKTOR UNGGULAN DI KOTA LANGSA - Dila Wulandari; Relensia Irda; Maylina Destriani Br Milala (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to identify the leading sectors in Kota Langsa as an effort to support regional economic growth. The analytical method employed involves the identification of leading sectors based on the Gross Regional Domestic Product (GRDP) data for the period 2018-2022. By using the location quotient and shift-share approaches, the research findings reveal that there are 12 leading sectors in Kota Langsa. These sectors include the processing industry, Water Supply, Waste Management, Recycling, Construction, Wholesale and Retail Trade; Repair of Motor Vehicles and Motorcycles, Transportation and Warehousing, Accommodation and Food Services, Information and Communication, Financial and Insurance Services, Real Estate, Company Services, Health and Social Activities, and finally, the Other Services sector..